Pembuatan Katalog Produk Desa Wisata Bantaragung Berbasis QR Code untuk Mendukung Penjualan - Dewi Melati; Agus Wibowo; Amna Amna; Vita Evelini Handayani Sinaga; Agus Herwanto (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This Community Service (PkM) activity aimed to assist village SME actors in creating a digital product catalog and QR Code that can be directly placed on stalls, product packaging, or promotional media. The methods used included field observation, interviews with tourism village managers and SME actors, catalog creation using Canva, storage on Google Drive, QR Code creation via me-qr.com, hands-on training, and questionnaire-based evaluation. The activity was held on May 8–9, 2026, and was attended by SME actors, Pokdarwis managers, and village residents. As a result, 5 SME products were documented in a 10-page digital catalog, 5 QR Codes were created and placed at strategic locations, and 2 ready-to-use product promotion posters were handed over to partners. The questionnaire evaluation showed an average satisfaction score of 3.85 out of 4 (very good category). SME actors stated that the QR Code-based catalog helped them promote their products more easily and made their products appear more professional in the eyes of tourists.